2019
DOI: 10.1063/1.5061682
|View full text |Cite
|
Sign up to set email alerts
|

High-Tc superconducting THz emitters fabricated by wet etching

Abstract: We studied the etching of small crystals of the high-Tc superconductor Bi2Sr2CaCu2O8+δ (Bi2212) with various dilute compositions of hydrochloric and nitric acids. A particular mixture of those acids was chosen to simultaneously fabricate multiple rectangular stand-alone Bi2212 mesa structures from a large, doubly-cleaved and doubly metallic-coated single crystal. The radiation characteristics of these devices were found to be very similar to stand-alone devices fabricated previously using dry-etching technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The heating generated in the process of ion-milling would affect the oxygen contents of the crystals. Recently, in order to improve the problems, we developed a wet etching method to make the Bi2212 crystal chips [39], [40]. We studied the etching characteristics of solutions which are mixture of HCl and HNO 3 .…”
Section: Development Of Thz-waves Emitting Devices Based On Bi2212 Cr...mentioning
confidence: 99%
“…The heating generated in the process of ion-milling would affect the oxygen contents of the crystals. Recently, in order to improve the problems, we developed a wet etching method to make the Bi2212 crystal chips [39], [40]. We studied the etching characteristics of solutions which are mixture of HCl and HNO 3 .…”
Section: Development Of Thz-waves Emitting Devices Based On Bi2212 Cr...mentioning
confidence: 99%
“…First of all, we will briefly describe the fabrication process of SAMs by the wet etching method as reported in our previous study. 37) A piece of Bi2212 single crystal grown by TSFZ-method 38) with a thickness of about 3-4 μm was obtained by cleaving the crystals using a Scotch tape. Both cleaved surfaces are coated by metallic thin films of Ag and Au by evaporation.…”
Section: Evaluation Of Etching Solutions For Thicker Bi2212 Samsmentioning
confidence: 99%
“…41) Furthermore, we reported that the undercut of mesa structures can be reduced by using a mixture solution of HNO 3 and HCl. 37) A wet etching method investigated here is based on the above previous studies and is applicable to the thicker SAMs up to roughly 10 μm. We evaluated four solutions with a higher concentration of HCl against our previous study 37) as shown in Table I and tried to find an appropriate one to make thicker SAMs.…”
Section: Evaluation Of Etching Solutions For Thicker Bi2212 Samsmentioning
confidence: 99%
See 2 more Smart Citations